Application of phycocyanin from Arthrospira (Spirulina) platensis as a hair dye - Kraseasintra, Oranit; Tragoolpua, Yingmanee; Pandith, Hataichanok; Khonkarn, Ruttiros; Pathom-aree, Wasu; Pekkoh, Jeeraporn; Pumas, Chayakorn (Frontiers in Marine Science, 2022)
Almost all of the current hair dye products today contain synthetic chemicals which may cause allergic reactions in some users. Phycocyanin (PC), a non-toxic cyanobacterial pigment, has been used in the food and cosmetics sectors. There are however, been a few reports on the application of phycocyanin as a hair colorant. This study aimed to assess the biological qualities of phycocyanin for use in natural hair dye product. Phycocyanin was tested for use against anti skin-pathogen (Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 14990, Methicillin-resistant Staphylococcus aureus (MRSA) DMST 20625, Propionibacterium acnes DMST 14916, Candida albicans DMST 21424, and Malassezia furfur M21), cytotoxicity of human immortalized keratinocyte (HaCaT) cells and tested for color fastness when used as a shampoo wash. According to the findings, Arthrospira (Spirulina) platensis phycocyanin has not shown the potential for use against anti-skin pathogenic microorganisms. While testing phycocyanin at the maximum doses of 2.5 mg/mL, the cytotoxicity test revealed that it is not hazardous to HaCaT cells. Bleached hair was dyed with a mixture of phycocyanin, natural developers, and mordants. A chroma meter was used to monitor color changes after shampoo washing. The findings revealed that phycocyanin has dyeability potential. 50% of the dyed hair color remained after 5 shampoo washes. The stability and color degradation of phycocyanin in hair dye powder formulation demonstrated good physical stability along with four cycles of heating/cooling. As a result, we can see that this pigment has the potential to be used as an active ingredient in natural hair dyes.